Queer Pop : Aesthetic Interventions in Contemporary Culture. - Papenburg, Bettina. (Queer Futures Series, 2024)
The Queer Futures series attends both to the future of the term 'queer' and to queer ways of imagining the future. It publishes critical interventions that harness insights from queer, trans*, feminist, gender, postcolonial, critical race, and disability theories to spotlight the flexibility and capaciousness of queer figurations and reimagine possible futures.